Conception and reality: Outcome of SARS-CoV-2 infection and vaccination among Hungarian IBD patients on biologic treatments. (April 2023) - Resál, Tamás; Matuz, Mária; Keresztes, Csilla; Bacsur, Péter; Szántó, Kata; Sánta, Anett; Rutka, Mariann; Kolarovszki-Erdei, Diána; Bor, Renata; Fábián, Anna; Szepes, Zoltán; Miheller, Pál; et al.
Abstract: Introduction: Inflammatory bowel disease potentially elevates the risk of infections, independently from age, while the disease activity and medical treatment(s) can also increase the risks. Nevertheless, it is necessary to clarify these preconceptions as well during the COVID-19 pandemic. Methods: An observational, questionnaire based study was conducted in Hungary between February and August 2021. 2 questionnaires were completed. The first questionnaire surveyed the impact of the pandemic on patients with biologic treatments and assessed the severity and outcome of the infection, whereas the second one assessed vaccination rate and adverse events. Results: 472 patients participated in the study. 16.9 % of them acquired the infection and 6.3 % needed hospitalization. None of them required ICU care. Male sex elevated the risk of infection (p = 0.008), while glove (p = 0.02) and mask wearing (p = 0.005) was the most effective prevention strategy. Nevertheless, abstaining from community visits or workplace did not have an impact on the infection rate. Smoking, age, and disease type did not elevate the risk. UC patients had poorer condition during the infection (p = 0.003); furthermore, the disease activity could potentially worsen the course of infection (p = 0.072). The different biological treatments were equally safe; no difference was observed in the infection rate, course of COVID-19. Azathioprine and corticosteroids did not elevate the infection rate. 28 patients (35.0 %) suspended the ongoing biologic treatment, but it had no impact on the disease course. However, it resulted in changing the current treatment (p = 0.004). 9.8 % of the respondents were sceptic about being vaccinated, and 90 % got vaccinated. In one case, a serious flare-up occurred. Discussion: Most patients acquired the infection at workplace. Biologic therapies had no effect on the COVID-19 infection, whereas male sex, an active disease, and UC could be larger threat than treatments. Vaccination was proved to be safe, and patient education is important to achieve mass vaccination of the population.